Effects of Sport-Based Interventions on Children’s Executive Function: A Systematic Review and Meta-Analysis - Contreras-Osorio, Falonn; Campos-Jara, Christian; Martínez-Salazar, Cristian; Chirosa-Ríos, Luis; Martínez-García, Darío (Brain sciences, 2021)
One of the most studied aspects of children’s cognitive development is that of the development of the executive function, and research has shown that physical activity has been demonstrated as a key factor in its enhancement. This meta-analysis aims to assess the impact of specific sports interventions on the executive function of children and teenagers. A systematic review was carried out on 1 November 2020 to search for published scientific evidence that analysed different sports programs that possibly affected executive function in students. Longitudinal studies, which assessed the effects of sports interventions on subjects between 6 and 18 years old, were identified through a systematic search of the four principal electronic databases: Web of Science, PubMed, Scopus, and EBSCO. A total of eight studies, with 424 subjects overall, met the inclusion criteria and were classified based on one or more of the following categories: working memory, inhibitory control, and cognitive flexibility. The random-effects model for meta-analyses was performed with RevMan version 5.3 to facilitate the analysis of the studies. Large effect sizes were found in all categories: working memory (ES −1.25; 95% CI −1.70; −0.79; p < 0.0001); inhibitory control (ES −1.30; 95% CI −1.98; −0.63; p < 0.00001); and cognitive flexibility (ES −1.52; 95% CI −2.20; −0.83; p < 0.00001). Our analysis concluded that healthy children and teenagers should be encouraged to practice sports in order to improve their executive function at every stage of their development.